2021
DOI: 10.1186/s13102-021-00298-w
|View full text |Cite
|
Sign up to set email alerts
|

Cross-education and detraining effects of eccentric vs. concentric resistance training of the elbow flexors

Abstract: Background Unilateral resistance training increases the strength of the contralateral non-trained homologous muscles known as the cross-education effect. We tested the hypothesis that unilateral eccentric resistance training (ET) would induce greater and longer-lasting cross-education effect when compared with concentric resistance training (CT). Methods Young (20–23 y) participants were allocated to ET (5 males, 4 females) or CT (5 males, 4 female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 33 publications
1
19
0
Order By: Relevance
“…This study showed that the decrease in ROM caused by ECC exercise was associated with an increase in tissue hardness, and the decrease in muscle strength was associated with muscle soreness. As described above, the ECC emphasized a larger muscle strength increase and muscle hypertrophy when compared with other types of training [ 3 , 4 , 5 ]. Nevertheless, acutely and up to the time that the muscle is fully recovered, ECC exercise could negatively affect athletic performance, reduce training quality, adherence to resistance, and likely cause higher injury prevalence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study showed that the decrease in ROM caused by ECC exercise was associated with an increase in tissue hardness, and the decrease in muscle strength was associated with muscle soreness. As described above, the ECC emphasized a larger muscle strength increase and muscle hypertrophy when compared with other types of training [ 3 , 4 , 5 ]. Nevertheless, acutely and up to the time that the muscle is fully recovered, ECC exercise could negatively affect athletic performance, reduce training quality, adherence to resistance, and likely cause higher injury prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…The time course of changes in muscle strength ROM, DOMS, swelling, and blood creatine kinase (CK) in the day after intense eccentric exercise varies, and the loss of muscle strength and ROM and increase in muscle soreness could peak 24–48 h after intense ECC exercise [ 1 ]. Additionally, the ECC emphasized that resistance training could cause larger muscle-strength increase and muscle hypertrophy [ 3 , 4 , 5 ]. Since such impairments after intense ECC exercise could influence athletic performance, reduce training quality, reduce adherence to resistance training, and result in a higher injury prevalence, it is necessary to control the loss of muscle strength and ROM and increase muscle soreness after intense ECC exercise.…”
Section: Introductionmentioning
confidence: 99%
“…A familiarization session was set 1 week prior to the baseline measurements, and all participants practiced the MVC-ISO, MVC-CON, and MVC-ECC torque measurements on both trained (dominant) and non-trained (non-dominant) arms. The resistance training was performed twice a week with a rest period of at least 48 h between sessions for 5 weeks ( Sato et al, 2021 ). All participants were instructed to refrain from any systematic training outside the study for the experimental period.…”
Section: Methodsmentioning
confidence: 99%
“…Each participant lay in the supine position on a bed with the arms placed at each side and the forearm supinated while relaxing the arms. Ultrasound measurements of the transverse-axis were repeated twice, and the MT of biceps brachii plus brachialis was measured as the distance from the inner edge of the fascia to the humerus ( Abe et al, 2000 ; Sato et al, 2021 ). The average of the two measurements was calculated for each site and used for further analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Many factors affect muscle strength and hypertrophy in resistance training. Although further discussion is needed regarding the effect of muscle contraction mode, it is well known that resistance training emphasizing eccentric contraction (ECC) has a superior effect on muscle strength and hypertrophy than resistance training emphasizing concentric contraction (Katsura et al, 2019;Sato et al, 2021;Tseng et al, 2020). Although ECC resistance training can be applied in sports and medical fields, delayed onset muscle soreness (DOMS) often occurs as an adverse effect.…”
Section: Introductionmentioning
confidence: 99%